The Application of Carbohydrate-Reduction in General Practice: A Medical Audit - Hawkins, Marcus A; Zinn, Caryn; Delon, Christine (AOSIS, 2023)
Background: Carbohydrate-reduction has been used successfully in the management of conditions arising from insulin resistance. Aim: In this audit, the authors report on metabolic outcomes from 72 patients in primary care who have undergone counselling using a low-carbohydrate dietary approach. Setting: This audit took place in a family medical practice located in a relatively affluent suburb in East Auckland, New Zealand. Methods: Patients adopted a carbohydrate reduction diet with regular follow-up and monitoring of health parameters. Results: The mean duration of observation was 21.5 (± 10.4) months. On average, patients lost 11 (± 8.4) kg, with 17% attaining a healthy body mass index (BMI). Four out of five patients reversed prediabetes over 20.8 (± 13.4) months. Twenty-five per cent (28/113) of the practice population with type 2 diabetes (T2DM) participated, of which 64% reversed and 11% remitted T2DM over 20.7 (± 11.8) months. Two patients stopped insulin and 10 reduced or stopped other diabetes medications. Nearly 35% (25/72) of participants were initially hypertensive. Thirty-six per cent (9/25) normalised systolic blood pressure (SBP), 28% (7/25) normalised diastolic blood pressure (DBP), and 16% (4/25) normalised both SBP DBP. Sixty-four per cent reduced or stopped some or all antihypertensive medication. There was a mean reduction in SBP of 10.3 (± 17.7) mmHg and DBP of 4.8 (± 12.3) mmHg over 23.8 (± 9.0) months. Lipid changes were generally favourable, with 52% normalising triglycerides, 61% increasing high density lipoprotein cholesterol (HDL-C) to greater than 1.0 mmol/L, and 39% reducing low density lipoprotein cholesterol (LDL-C). Discussion: This real-world audit aligns with published data on the benefits of carbohydrate reduction. Conclusion: Effective management of prediabetes using CR might represent the biggest ‘bang for buck’ with a potential reduction in weight and prevention of diseases related to IR. Contribution: A low-carbohydrate dietary approach in primary care may serve as a realistic option for improving multiple health outcomes.
Keywords: 4203 Health Services and Systems; 32 Biomedical and Clinical Sciences; 42 Health Sciences; Prevention; Cardiovascular; Clinical Research; Obesity; Diabetes; Nutrition; Metabolic and endocrine; 3 Good Health and Well Being